Implementation of Regional Decentralization To The Implementation of Autonomic Village - Mammarella Ramadhan A.; Feni Rosalia (Journal of Public Administration and Government, 2022)
Village autonomy refers to the authority granted to a village to independently administer and manage its affairs without interference from higher levels of government, such as the sub-district, district, or central government. In practice, the significance of village autonomy lies in determining the village's location, autonomy level, and integration into the regional government structure. However, conflicts between the central government and regional authorities often highlight the ongoing struggle for defining the extent of village autonomy. In reality, village autonomy is often more of a symbolic or theoretical concept, as it is frequently affected by the interventions of higher-level governments. The authorities vested in villages are partially controlled by supra-village governing bodies. Additionally, there is ongoing debate surrounding whether the concept of village autonomy aligns with that of regional autonomy, leading to uncertainty about its precise form and implementation. While cities receive full development support through state budget allocations, rural areas are developed through a combination of government funds and local community efforts. Consequently, village autonomy is not genuinely independent in the sense of being a fully self-governing community or solely reliant on community self-help mobilization. Instead, it should be understood as a form of local self-government, where villages possess a degree of authority and status as autonomous regions within the framework of the Unitary State of the Republic of Indonesia (NKRI).